Effect of eye massaging device towards brain rhythms - A. Mansor, F.; Sudirman, R. (International Journal of Engineering and Technology, 2018)
This study aimed to examine the effectiveness of the eye massaging device in promoting mind relaxation state based on alpha rhythm in brain. This study has been conducted involving 35 participants whose their brain signals were captured by an electroencephalography (EEG) machine whilst they undergoing resting state, eye massaging session and visual tasks designed to induced stress. The signal is analyzed using Discrete Wavelet Transform (DWT) and the major concern of the study, relative power of alpha was extracted from channel point O1 and O2. T-test analysis used to validate the differences of relative alpha power produced before and after using the device. Based on the results, the average values of relative alpha power collected for EEG signals before using the eye massaging device has been increased for both channel (O1: before = 17.601, after = 19.765, O2: before = 12.577, after = 14.783) with an increment of 12.29% and 17.54% respectively. However, there is no enough evidence to prove that using the device give positive effect on improving participantâ€™s relaxation state as there is only have 51.5% and 58.4% chances that the device might worked on mind relaxation state.Â Â